Paradigms in theology - W.J. Ouweneel (Acta Theologica)
My present starting-point, not worked out here (cf. extensively Ouweneel 1993), is that all scientific activity, even all human action is founded in a central-religious ground-motive (fundamental driving-force of a religious-spiritual nature). It is my view that scientific, including theological activity necessarily demands such a ground-motive, and that every ground-motive roots in the human heart. That is, all theological work, carried out within a certain paradigm, is entirely determined by the central-religious ground-attitude assumed a priori with respect to the bible by the theological communicty working within that paradigm.